Modeled rapid adjustments in diurnal temperature range response to CO2 and solar forcings. Issue 5 (14th March 2013) - Jackson, Lawrence S.; Forster, Piers M.
Abstract : [1] We used the National Center for Atmospheric Research single column climate model to determine if rapid adjustments to surface heat fluxes contribute to a change in skin surface or surface air diurnal temperature range (DTR) under 2 × CO2 and −2% solar forcings. An ensemble of model runs was employed with locations selected to represent a range of different climatic conditions and with forcing implemented hourly throughout the diurnal cycle. The change in skin surface DTR and surface energy fluxes during the 3 days after forcing were used to quantify the rapid adjustment response and temperature related feedback. Averaged over all locations, skin surface DTR reduced by 0.01°C after CO2 forcing and included a rapid adjustment to skin surface DTR of −0.12°C. Skin surface DTR reduced by 0.17°C after solar forcing and included a rapid adjustment of −0.01°C. The rapid adjustments in skin surface DTR were associated with rapid adjustments in surface sensible and latent heat fluxes necessary to balance the energy budget immediately after forcing. We find that the sensitivity of skin surface DTR to mean temperature related feedback is the same for CO2 and solar forcings when skin surface DTR rapid adjustments are allowed for. Rapid adjustments played a key role in the geographic variation of the skin surface DTR response to forcing. Our results suggest that diurnal variations in trends of downwelling longwave radiation and rapid reductions in DTR associated with CO2 forcing potentially contributed to the observed global trend in surface air DTR. Key Points: Changes in DTR are sensitive to diurnal variations in CO2 forcing Rapid adjustments in surface heat fluxes affect DTR response DTR trends since 1950 influenced by these diurnal scale responses